College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 2 - Section 2.2 - Graphs of Equations in Two Variables; Intercepts; Symmetry - 2.2 Assess Your Understanding: 1



Work Step by Step

Solve the equation: $2(x+3)-1=-7$ First, we add 1 to both sides: $2(x+3)-1+1=-7+1$ $2(x+3)=-6.$ Now we divide both sides by 2: $2(x+3)/2=-6/2$ $x+3=-3.$ Now, we subtract 3 from both sides: $x+3-3=-3-3.$ So, $x=-6.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.